E-Learning and Cross-Border Higher Education: Post-Pandemic Potentials and Challenges - Donnie, Adams; Chuah, Kee Man (Nova Science Publishers, 2022)
The impact of COVID-19 pandemic on higher education goes beyond campus closures and disruption in programme delivery. The crisis has indirectly allowed higher education institutions to re-examine their existing programme structure in order to be more flexible and accessible to students both locally and internationally. Such need has triggered a new interest in assessing the use of e-learning in enhancing cross-border higher education, which was traditionally restricted mainly to campus based physical experience. This chapter discusses the challenges and potentials of implementing cross-border higher education through e-learning mode in the context of post-pandemic higher education ecosystem. The transition to online learning during the pandemic as faced by higher education institutions has elevated the interest in maximizing the roles that e-learning could play in higher education. While e-learning has the potential to allow more cross-border programmes to be offered internationally via virtual mobility, issues surrounding quality assurance, infrastructure and diversity remain critical to be addressed. Higher education institutions should not emphasize solely on penetrating new markets without taking measures to deal with the issues mentioned. On the whole, this chapter would serve as a good reference to relevant stakeholders in uncovering the hidden potentials of e-learning in crossborder higher education and evaluating its challenges.